Sosialisasi Blog Sebagai Media Mengasah Kemampuan Menulis Dan Sarana Berbagi Ilmu Bagi Siswa SMA - Siregar, Yunita Sari; Mufida Khairani; Nurjamiyah (Unity Academy, 2023)
In the era of increasingly sophisticated and developing technology, the use of computer-based technology is not only used in the world of education and offices, but is widely used as a medium of learning and digitalization for students. There are many applications and software that can be used to support digital-based learning for students at school such as blog media. Blog is a form of web application that can contain writing that can be accessed by anyone who wants to get information. Where this student blog will contain various student experiences in learning at school. Peng activities. This community service activity was carried out at Nur Azizi Tanjung Morawa High School, Deli Serdang Regency by utilizing Blogs as a medium to hone writing, where the participants of this activity were 30 high school students. The purpose of this activity is to increase insight, knowledge and experience for high school students in web writing learning activities and sharing information and learning experiences for others. The results of this training activity are expected by high school students to increase the use and use of digitalization-based information technology as a medium to hone writing and a means of sharing learning knowledge through Blog media.